WASIAT DAN HUTANG DALAM WARISAN - Nuzha Nuzha (Fakultas Syariah IAI Muhammadiyah Bima, 2017)
When someone dead, there are two things related to heiress, the testament and debt. Pay the debt is obligated before the heiress divide by the join heirs. The testament consist of testament which given to someone except the join heirs, meanwhile the testament wajibah is given to child by adoption who does not receive the testament also to grand child whom parents dead quick or same with testament. Both of concepts has the law, requirements and problems which often face in social life with different condition